Click 'n' Pay / Alethia Subil... [et al.] - Subil, Alethia; Majinin, Norsariana; Arip, Izni Najwa; Ag Dullah, Ag Nizam; Utu, Mohd. Hafifi; Supian, Mohd. Redzuan (2015)
The idea was thought of when our General Manager, Alethia Subil, whe she thought about the times she would go grocery shopping with her grandmother. Her Grandmother woult not be able to pick her groceries and would just stand at a corner and wait for the groceries to be done and proceed to payment. How nice would it be if there would be some sort of assistance to the grocery selecting and save that time to spend more quality time together.